A customized H-infinity algorithm for underwater navigation system: With experimental evaluation. (15th January 2017) - Emami, Mehdi; Taban, Mohammad Reza
Abstract: In this paper, an integrated navigation system based on H-infinity filter is proposed for improving the performance of underwater navigation system. The proposed navigation system consists of a package with a triad of accelerometers and an Attitude and Heading Reference System (AHRS) as the main system and a Doppler Velocity Log (DVL) as an auxiliary system. In this system, the dynamic and measurement models are defined in such a way by which a H-infinity based integrated navigation system is derived. In addition, according to the specific dynamic of discussed vehicle, a scheme is proposed for estimating the performance bound parameter of H-infinity filter. The proposed system becomes robust versus the system modeling errors and noise uncertainty in comparison with the conventional Kalman Filter (KF). Furthermore, it can be effectively decrease the effect of the DVL's outlier data. The performance of the proposed system is evaluated through several sea tests using an Autonomous Underwater Vehicle (AUV). Furthermore, the conventional Dead Reckoning (DR) and KF algorithms are utilized for comparison. The experimental results demonstrate the superior performance of the proposed system compared with the conventional algorithms. Abstract : Highlights: An improved integrated navigation system based on H-infinity filter is proposed. Estimation of the performance bound parameter of H-infinity filter is suggested. The proposed system is robust versus the system modeling errors and noise uncertainty The proposed system can effectively decrease the effect of the DVL's outlier data. The performance of the proposed system is evaluated through several sea tests.